Post-control of agricultural subsidies provided by EU - Ficzere Nagymihály, Kornélia; Czencz, László (Acta Agraria Debreceniensis, 2008)
The greatest part of the incomes (nearly fifty percent) of the European Union is spend on the agriculture and the agricultural policy is the most complex field among the common policies. In Hungary the payments from Guarantee Section of EAGGF are carried out by one Paying Agency (Agricultural and Rural Development Agency), the post audit of payments are carried out by Investigation Network of Hungarian Customs and Finance Guard on the base of Council Regulation No. 4045/89. A full co-operation of the business operators is expected during the audit, which means the presentation of the complete accounting file related to subsidies. To avoid declarations on irregularities during the audit and the following order on repayment of the subsidy, all requirements of gaining subsidies have to be kept. The state authorities, in present case the customs authority should pay special attention to the risk analysis activity, and its harmonising with the proposals and guidelines of the Commission. Getting acquainted and using in practice the actual requirements and proposals of the Commission’s guidelines is expected at all levels of the control service of the HCFG, but primarily the Special Service has to continue its present practice in this field. The measures mentioned above, respectively the effective period taken under analysis teens from the date of accession until June 2005.